Bioderecho, ‘dilema del doble uso’ y libertad de la investigación científica (2020)
This article aims to legally explore the dual-use dilemma, as referred to two areas: one, which is more 'traditional:is the field of nuclear science and technology, and the other one, which is a new emerging area, is synthetic biology. One important conclusion will be that the freedom of scientific research, which is central in this context, has to be protected, but at the same time the other rights and freedoms atstake cannot be 'suppressed' or 'sacrificed'.